Pengaruh Penggunaan Baamboozle sebagai Media Pembelajaran Informatika terhadap Hasil Belajar Siswa Kelas X di SMKN 1 Kuningan (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to determine the effect of Baamboozle as a learning medium on the learning outcomes of class X students at SMKN 1 Kuningan. This research uses a quantitative research type. In this study, the experimental method is employed. The design applied in this research is a pre-experimental study with a One Group Pretest-Posttest Design. The population used consists of all class X students at SMK Negeri 1 Kuningan, totaling 640 individuals. The sample used in this study is the class X of Agribusiness Crop/Agribusiness Food Crops and Horticulture (ATPH) 1 as the experimental class, consisting of 30 students, including 23 males and 7 females. The instruments used were pretest, posttest, and questionnaires. The data analysis techniques employed were validity test, normality test, hypothesis test, reliability test, and data tabulation. This research was conducted at SMKN 1 Kuningan with a sample of 30 students from class X ATPH 1. The findings of this study are: (1) the students' learning outcomes in Informatics before using the Baamboozle media were far from the KKM (Minimum Competency Criteria) with an average of 62.66; (2) the students' learning outcomes in Informatics after using the Baamboozle media showed an improvement with an average score of 77.33; (3) Based on the hypothesis testing/paired sample t-test, there is an effect on students' learning outcomes before and after using Baamboozle media as a learning tool